Strategies for teaching oral communication to intermediate level adults, learning english as a foreign language in a language center - Serrano Martínez, Kenia Nayósqui; Juarez, Elizabeth; Araúz, Clemente (David, Panamá : UDELAS, 2009)
Of all the four skills (listening, speaking, reading and writing), speaking seems intuitively the most importan: people who know a language are referred to as "speakers" of that language, in this way we have seem manu foreign language learners who are interested in learningnto speak, mainly adults who are looking for a variety of opportunities, abilities and quality that a new language can offer to them.
CONTENT TABLE DEDICATION ACKNOWLEDGMENT INTRODUCTION CHAPTER I RESEARCH PROBLEM CHAPTER II THEORICAL FRAME CHAPTER IIIMETHODOLOGY OF RESEARCH CHAPTER IV OUTCOMES CHAPTER V CONCLUSIONS AND RECOMMENDATIONS CHAPTER IV BIBLIOGRAPHY AND ANNEX
Incluye Content Table
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- STRATEGY; FACULTAD DE EDUCACIÓN SOCIAL; DEPARTAMENTO DE INGLES; LICENCIATURA EN DOCENCIA EN INGLÉS